Systematic analysis and exploration of molecular mechanisms of psoriasis and metabolic comorbidities - LI Sijia; CAO Zhejia; ZHENG Siqi; CHENG Shuqiong; ZHONG Meizhen; ZHENG Yue; HUANG Xiaowen (Pifu-xingbing zhenliaoxue zazhi, 2025)
Psoriasis is strongly associated with metabolic disorders. Effective management of metabolic dysfunction and individualized treatment strategies for different comorbidities are crucial for preventing disease progression and improving the overall health of psoriatic patients. However, biomarkers that reliably reflecting metabolic status and comorbid metabolic diseases in psoriasis remain limited. The bidirectional relationship between psoriasis and metabolic disorders stems primarily from shared pathophysiological mechanisms, which may mutually activate disease pathways and exacerbate inflammation. This review summarizes the metabolic comorbidities associated with psoriasis and explores potential biomarkers and molecular mechanisms in depth. The goal is to provide new insights for the diagnosis, risk assessment, and personalized treatment of metabolic complications in psoriatic patients.